Efeito dos hábitos comportamentais e gordura corporal sobre indicadores de risco cardiovasculares entre adolescentes: estudo de coorte de 12 meses - Cayres, Suziane Ungari [UNESP] (2015)
Objectives To analyze, after 12 months, (i) the alterations in the behavioral habits and body fat under some indicators of the cardiovascular risk among adolescents, as well, (ii) if these effects of the behavioral habits and body fat were independents. In addition, from cross-sectional data were analyzed to (i) the relationship between physical activity indicators on some cardiovascular risk outcomes; (ii) the relationship between the frequency of breakfast consumption on cardiovascular risk factors, inflammatory and metabolic markers; (iii) the relationship between parasympathetic indices and resting heart rate with cardiovascular risk markers, and (iv) the relationship between hsCRP and lipid profile, blood flow and blood intima-media thickness between prepubertal adolescents were stratified according to the engagement sports practices.Methods Cohort study of 12 months, carried out in Presidente Prudente city, State of Sao Paulo. The inclusion criteria were: (i) age between 11 and 14 years old; (ii) enrolled in the school unit of elementary education; (iii) absence of any known disease; (iv) without drug consumption. All adolescents participated in each measure: (i) behavioral habits; (ii) body fat; (iii) blood pressure; (iv) heart rate resting; (v) heart rate variability; (vi) intima-media thickness; (vii) anthropometry; (viii) lipid profile; (ix) high sensitivity C reactive protein; (x) eating habits; (xi) blood flow and (xii) biological maturation. The relationship among variables were tested by correlation, and, when necessary, it were made some adjustments. Significant relationships were inserted in the multivariate model (linear regression). Teste t Student and variance analysis (ANOVA one way) established comparison among mean values. Significance statistical (p-valor) lower than 5% were considered statically different. All analyses were performed in the software BioEstat (version 5.0, Tefé, Amazonas). Results In all, 120...